Integrating CAR T-Cell Therapy and Transplantation: Comparisons of Safety and Long-Term Efficacy of Allogeneic Hematopoietic Stem Cell Transplantation After CAR T-Cell or Chemotherapy-Based Complete Remission in B-Cell Acute Lymphoblastic Leukemia - Zhao, Yan-Li; Liu, De-Yan; Sun, Rui-Juan; Zhang, Jian-Ping; Zhou, Jia-Rui; Wei, Zhi-Jie; Xiong, Min; Cao, Xing-Yu; Lu, Yue; Yang, Jun-fang; Zhang, Xian; Lu, Dao-Pei; et al. (Frontiers in Immunology, 2021)
Patients often undergo consolidation allogeneic hematopoietic stem cell transplantation (allo-HSCT) to maintain long-term remission following chimeric antigen receptor (CAR) T-cell therapy. Comparisons of safety and efficacy of allo-HSCT following complete remission (CR) achieved by CAR-T therapy versus by chemotherapy for B-cell acute lymphoblastic leukemia (B-ALL) has not been reported. We performed a parallel comparison of transplant outcomes in 105 consecutive B-ALL patients who received allo-HSCT after achieving CR with CAR-T therapy (n=27) or with chemotherapy (n=78). The CAR-T-allo-HSCT group had more patients in second CR compared to the chemotherapy-allo-HSCT group (78% vs. 37%; p<0.01) and more with complex cytogenetics (44% vs. 6%; p<0.001) but the proportion of patients with pre-transplant minimal residual disease (MRD) was similar. The median follow-up time was 49 months (range: 25-54 months). The CAR-T cohort had a higher incidence of Grade II-IV acute graft-versus-host disease (aGVHD 48.1% [95% CI: 46.1-50.1%] vs. 25.6% [95%CI: 25.2-26.0%]; p=0.016). The incidence of Grade III-IV aGVHD was similar in both groups (11.1% vs.11.5%, p=0.945). The overall incidence of chronic GVHD in the CAR-T group was higher compared to the chemotherapy group (73.3% [95%CI: 71.3-75.3%] vs. 55.0% [95%CI: 54.2-55.8%], p=0.107), but the rate of extensive chronic GVHD was similar (11.1% vs.11.9%, p=0.964). Efficacy measures 4 years following transplant were all similar in the CAR-T vs. the chemotherapy groups: cumulative incidences of relapse (CIR; 11.1% vs.12.8%; p=0.84), cumulative incidences of non-relapse mortality (NRM; 18.7% vs. 23.1%; p=0.641) leukemia-free survival (LFS; 70.2% vs. 64.1%; p=0.63) and overall survival (OS; 70.2% vs. 65.4%; p=0.681). We found that pre-transplant MRD-negative CR predicted a lower CIR and a higher LFS compared with MRD-positive CR. In conclusion, our data indicate that, in B-ALL patients, similar clinical safety outcomes could be achieved with either CD19 CAR T-cell therapy followed by allo-HSCT or chemotherapy followed by allo-HSCT. Despite the inclusion of more patients with advanced diseases in the CAR-T group, the 4-year LFS and OS achieved with CAR T-cells followed by allo-HSCT were as remarkable as those achieved with chemotherapy followed by allo-HSCT. Further confirmation of these results requires larger, randomized clinical trials.